2013
DOI: 10.6018/analesps.29.1.161871
|View full text |Cite
|
Sign up to set email alerts
|

Drogodependientes vs. usuarios de salud mental con trastornos de personalidad: su relación con la calidad de vida, la psicopatología en Eje I, el ajuste psicológico y dinámica familiar

Abstract: La muestra la componen 68 pacientes que presentan un trastorno de la personalidad de los que el 57.4 % son drogodependientes en tratamiento en un centro ambulatorio de atención a las drogodependencias y el 42.6 % son usuarios de un centro ambulatorio de salud mental que no presenta trastornos adictivos. Los resultados muestran que no existen diferencias significativas en calidad de vida ni gravedad de ajuste psicológico entre los pacientes en función de la drogadicción. Las diferencias parecen estar vinculadas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
1
1
0
2
Order By: Relevance
“…As a last goal, it is noted that psychological distress is relevant to understand the dimension of motivation, focused on patients' motivation for treatment when initiating the therapeutic process. As in previous studies (Martínez-González et al, 2013;, we confirmed that psychological distress plays a relevant role in motivation for treatment, to the extent that it predicts a high percentage of the variance of motivation for treatment, the precursor of the demand for therapeutic attention. However, psychological distress does not predict preparation or readiness for change.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…As a last goal, it is noted that psychological distress is relevant to understand the dimension of motivation, focused on patients' motivation for treatment when initiating the therapeutic process. As in previous studies (Martínez-González et al, 2013;, we confirmed that psychological distress plays a relevant role in motivation for treatment, to the extent that it predicts a high percentage of the variance of motivation for treatment, the precursor of the demand for therapeutic attention. However, psychological distress does not predict preparation or readiness for change.…”
Section: Discussionsupporting
confidence: 89%
“…The motivational level of the patient who initiates treatment seems to be influenced by the degree of psychological discomfort or distress, as a factor that impels him/her to seek therapeutic help (Martínez-González et al, 2013). In the case of drug treatment, distress is associated with drug consumption, so the disappearance of the discomfort that accompanies abstinence can substantially decrease motivation for treatment, even precipitating therapeutic dropout (Miller, 1985;Mulder et al, 2014).…”
mentioning
confidence: 99%
“…Nível VI Opiniões de especialistas, relatos de experiência, consensos, regulamentos e legislação. 25,27,31,[33][34][35][37][38][39] e QVRS (12,16,(18)(19)(20)(21)(22)(23)26,28,30,32,36,(40)(41)(42)(43) . Somente um estudo utilizou instrumento de QVRS específico para TUS (29) , embora que três dos estudos selecionados referiam-se à validação dessas escalas (12,24,38).…”
Section: Metodologiaunclassified
“…Este posee adecuadas propiedades psicométricas y mide 8 dimensiones: abuso/dependencia de alcohol, juego patológico, adicción a sustancias, trastornos de la alimentación, adicción a Internet, adicción a videojuegos, gasto compulsivo y adicción al sexo. El instrumento fue utilizado posteriormente en estudios con muestras de adultos, para la detección precoz de conductas adictivas (Rodríguez, Pedrero, Fernández, Gallardo, & Sanz, 2009), detección de trastornos en el control de impulsos en pacientes con trastornos de personalidad (Martínez-González, Becoña-Iglesias, & Munera-Ramos, 2013), y para el estudio de sujetos con problemas de adicción y uso problemático del internet (Navas, Torres, Cándido, & Perales, 2014;Pedrero, 2010).…”
unclassified